Drug-induced QT Prolongation Atlas (DIQTA) for enhancing cardiotoxicity management. Issue 3 (March 2022) - Li, Shihai; Xu, Zili; Guo, Mingkun; Li, Menglong; Wen, Zhining
Highlights: A curated drug-induced QT prolongation atlas was developed. A schema was proposed to stratify the risk of drug-induced QT prolongation. Diverse information of QT prolonging drugs was collated in the database. The database can be helpful for investigating the drug-induced torsade de pointes. Abstract: Drug-induced prolongation of the QT interval is common in a variety of pharmaceutical treatments and can lead to serious clinical outcomes. Although substantial efforts have been made to prevent drug-induced QT interval prolongation, the lack of a centralized data source remains the main obstacle to further study of the underlying mechanism and the development of effective prediction strategies. To fill this gap, we propose a schema for stratifying the risk of marketed QT prolonging drugs based on US Food and Drug Administration (FDA)-approved drug labeling and developed a Drug-Induced QT Prolongation Atlas (DIQTA). Potential application of DIQTA was shown by precision dosing in off-label use and therapeutic strategy optimization, as well as the facilitation of artificial intelligence (AI)-based modeling in predictive toxicity.